Zastosowanie biblioterapii w leczeniu zaburzeń seksualnych. Doniesienie z wybranych badań - Chatzipentidis, Kiriakos (eBooki.com.pl, 2014)
The article is a review of research into uses of a cognitive-behavioral bibliotherapy in the treatment of sexual dysfunctions. Analysis of articles from the EBSCO databases, Science Direct, ProQuest indicates that bibliotherapy is successfully used in the treatment of sexual dysfunction, especially in Hypoactive sexual desire disorder  (HSDD) as an effective, widely available and cost-effective adjunctive therapy in the treatment of women in particular.
Keywords: sexual dysfunction; cognitive-behavioral bibliotherapy; Sexual Therapy; sexology; bibliotherapy